Chapter Russia in the Global Parliamentary Moment, 1905-1918: Between a Subaltern Empire and an Empire of Subalterns - Sablin, Ivan (Dialectics of the Global, 2020)
This volume adds to the plurality of global histories by locating the global through its articulation and manifestation within particular localities. It accomplishes this by bringing together interlinked case-studies that analyse various temporal and spatial dimensions of the global in the local and the interactions between the local and the global.